Cancer nanomedicine: mechanisms, obstacles and strategies. (23rd July 2018) - Li, Huafei; Jin, Hai; Wan, Wei; Wu, Cong; Wei, Lixin
Targeting nanoparticles to cancers for improved therapeutic efficacy and decreased side effects remains a popular concept in the past decades. Although the enhanced permeability and retention effect serves as a key rationale for all the currently commercialized nanoformulations, it does not enable uniform delivery of nanoparticles to all tumorous regions in all patients with sufficient quantities. Also, the increase in overall survival is often modest. Many factors may influence the delivering process of nanoparticles, which must be taken into consideration for the promise of nanomedicine in patients to be realized. Herein, we review the mechanisms and influencing factors during the delivery of cancer therapeutics and summarize current strategies that have been developed for the fabrication of smart drug delivery systems.